Gastric Ectopic Pancreas: Not Always an Innocent Bystander - Kalaitzakis, Evangelos; Elebro, Jacob; Johansson, Jan (JOP. Journal of the Pancreas, 2013)
No abstract available. Image: Subepithelial lesion in the gastric antrum.